KOMPETENSI MANAJERIAL KONSELOR PADA LAYANAN KONSELING KELOMPOK - Riswanto, Dody (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
The purpose of this study was to determine the managerial ability of the counselor in implementing group counseling at school. The research method used is qualitative, data analysis used is drawing conclusions based on Lawrence's theory. The results of the research and discussion are conflict, resistance, confrontation and imbalance of group members as the main problems in group dynamics, the managerial ability of the counselor in organizing, leading, directing and organizing all group members to be successful indicators of group counseling success.